Podcast
Questions and Answers
A + 0 = ______
A + 0 = ______
a
W + (wxyz) = ______
W + (wxyz) = ______
w
(x + y)(x + y) = ______
(x + y)(x + y) = ______
x + y
A+ 0 =
A+ 0 =
Signup and view all the answers
(a+b)(a+b) =
(a+b)(a+b) =
Signup and view all the answers
A(a+b+c+ ...) =
A(a+b+c+ ...) =
Signup and view all the answers
F[a,b,(ab)] =
F[a,b,(ab)] =
Signup and view all the answers
(w+x+y+z)y =
(w+x+y+z)y =
Signup and view all the answers
(x + y)(x + y) =
(x + y)(x + y) =
Signup and view all the answers
W+[w+(wx)] =
W+[w+(wx)] =
Signup and view all the answers
W+(wxyz) =
W+(wxyz) =
Signup and view all the answers
Xz + xy + zy =
Xz + xy + zy =
Signup and view all the answers
(x+z)(x+y)(z + y) =
(x+z)(x+y)(z + y) =
Signup and view all the answers
Flashcards
a + 0 = a
a + 0 = a
The output is always the variable 'a'. Any variable added to a zero will always result in the original variable.
a • 0 = 0
a • 0 = 0
The output is always 0. Any variable multiplied by zero will always result in zero.
a + a = a
a + a = a
The output is always the variable 'a'. When a variable is added to itself, it is the same as having one of that variable.
a • a = a
a • a = a
Signup and view all the flashcards
a + ab = a
a + ab = a
Signup and view all the flashcards
a(a + b) = aa + ab
a(a + b) = aa + ab
Signup and view all the flashcards
(a + b)(a + b) = (a + b)^2
(a + b)(a + b) = (a + b)^2
Signup and view all the flashcards
a(a + b + c +... ) = a
a(a + b + c +... ) = a
Signup and view all the flashcards
f(a,b,ab)= a + b + ab = a + b
f(a,b,ab)= a + b + ab = a + b
Signup and view all the flashcards
f(a,b,ab)= a + b + ab = a + b
f(a,b,ab)= a + b + ab = a + b
Signup and view all the flashcards
f[a,b,(ab)]= a + b + c
f[a,b,(ab)]= a + b + c
Signup and view all the flashcards
y + yy = y
y + yy = y
Signup and view all the flashcards
xy + xy = xy
xy + xy = xy
Signup and view all the flashcards
x + yx = x
x + yx = x
Signup and view all the flashcards
(w + x + y + z)y = y
(w + x + y + z)y = y
Signup and view all the flashcards
(x + y)(x + y) = (x + y)^2
(x + y)(x + y) = (x + y)^2
Signup and view all the flashcards
w + [w + (wx)] = w
w + [w + (wx)] = w
Signup and view all the flashcards
x[x + (xy)] = x
x[x + (xy)] = x
Signup and view all the flashcards
x + x = x
x + x = x
Signup and view all the flashcards
x * x = x
x * x = x
Signup and view all the flashcards
w + (wxyz) = w
w + (wxyz) = w
Signup and view all the flashcards
w * (wxyz) = wxyz
w * (wxyz) = wxyz
Signup and view all the flashcards
xz + xy + zy = xy + zy
xz + xy + zy = xy + zy
Signup and view all the flashcards
(x + z)(x + y)(z + y) = (x + y)(z + y)
(x + z)(x + y)(z + y) = (x + y)(z + y)
Signup and view all the flashcards
x + y + xyz = x + y
x + y + xyz = x + y
Signup and view all the flashcards
Study Notes
Boolean Algebra Practice Problems
- a + 0 = a
- a * 0 = 0
- a + a = a
- a * a = a
- a + ab = a
- a + ab = a
- a(a + b) = a
- ab + ab = ab
- (a + b)(a + b) = a + b
- a(a + b + c + ...) = a
- For (11), (12), (13), f(a, b, c) = a + b + c
- f(a, b, ab) = a + b
- f(a, b, a-b) = a + b (Assuming the intended symbolic representation is for a NOT b which results in a + b)
- f[a, b, (ab)] = a + b (Assuming the intended symbolic representation for complement of ab which results in a + b)
- y + yy = y
- xy + xy = xy
- x + yx = x
- (w + x + y + z)y = wy + xy + yz
- (x + y)(x + y) = x + y
- w + [w + (wx)] = w
- x[x + (xy)] = x
- (x + x) = x
- (x + x) = x
- w + (wxyz) = w
- w * (wxyz) = wxy
- xz + xy + zy = x + y + z
- (x + z)(x + y)(z + y) = x + y + z
- x + y + xyz = x + y
Studying That Suits You
Use AI to generate personalized quizzes and flashcards to suit your learning preferences.
Related Documents
Description
Test your understanding of Boolean algebra with these practice problems. From basic identities to more complex expressions, this quiz covers a range of topics designed to enhance your skills. Perfect for students and enthusiasts looking to strengthen their grasp on the fundamentals.